Maqashid Al-Syari'ah dalam Regulasi Mediasi Mahkamah Agung: Studi Kasus Penyelesaian Konflik Waris di PA Sumedang: Maqashid Al-Syari'ah in the Supreme Court Mediation Regulation: A Case Study of Inheritance Dispute Resolution - Mohamad Athoillah; Tajul Arifin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
There has been a lot of research on Maqashid al-Syari'ah, but none of these studies have focused on disclosing the existence of Maqashid al-Syari'ah in the Regulation of mediation in court. This study aims to analyse the strength of Maqashid al-Syari'ah in mediation regulations and their application in the mediation process for inheritance disputes in the Religious Courts. This research applies a descriptive-analytical method; data were collected by observation, in-depth interviews with mediators, documentation and literature study, and then data analysis techniques were used. No previous research has specifically explored the spirit of Maqashid al-Syari'ah in Perma regarding mediation in court. The findings of this study show that Maqashid al-Syari'ah 's spirit in the Perma of Mediation Procedure in Court is powerful. However, the Maqashid al-Syari’ah spirit contained in the Supreme Court Regulation has not been successfully implemented in mediation in Religious Courts. The results of this research imply the necessity for mediators to master the Maqashid al-Syari'ah and its spirit contained in the Perma on Mediation Procedures in Court well and apply it in mediation.